The Social Epistemology of Engineered Agricultural Ecologies - Kendig, Catherine; Thompson, Paul B.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This open access collection of new interdisciplinary essays discusses philosophical and social implications of new biotechnologies, methods, and tools used in agriculture from a multispecies perspective. Contributors employ philosophy, sociology, and history of agriculture; agricultural ethics; philosophy of science; and science and technology studies to investigate agricultural research, farming practice, and agricultural policy. Chapters explore and critically discuss how mechanical, chemical, and genetic interventions reshape ecological relationships and agricultural knowledge by relying on case studies of interspecies interactions across different agriculturalized landscapes. These include careful examinations of the nature of dynamic causal relationships across microbial, macrobial, megaflora and faunal organismal communities; exploration of specific coevolved species of pollinators and field crops; and analyses of the epistemic and normative commitments that guide crop management decisions and shape methodological choices leading to the reengineering of land use. These analyses and case studies are intended to provide readers with a variety of conceptual tools through which the use of agricultural technologies might possibly be understood and debated .
Chapter 1: Introduction: Technological innovations in agriculture: a philosophy and sociology of science approach -- Chapter 2: What is soil, and what is it for? Social ontologies and social epistemologies of soil affordances and soil experiments -- Chapter 3:Dreaming the Butterfly: Engineered Ecologies and Fragile Futures -- Chapter 4: Agency and Relationships in Engineered Agricultural Ecologies -- Chapter 5: Treading Lightly, Agriculture, and Focality -- Chapter 6: Reframing Gene Editing in Crops: Unpacking Potential Solutions by Reconsidering the Questions Asked -- Chapter 7: Unpacking public engagement in agricultural biotechnology: the role of narratives and social epistemology in a deliberative workshop on gene editing in agriculture and food -- Chapter 8: A Risk-Based Agricultural Biotechnology Ethics in the Era of Gene Editing: What is New and What Is Not.
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Agriculture; Applied ethics; Technology -- Philosophy; Agricultural biotechnology; Agricultural genome mapping; Agricultural Ethics; Philosophy of Technology; Agricultural Biotechnology; Agricultural Genetics